Reusing end-of-life reverse osmosis membranes: Strategies, challenges, and future perspectives - Zeeshan Arshad; Muhammad Ashraf; Taha Demraoui; Tauqir Ahmad; Muhammad Bilal Asif; Niaz Ali Khan; Mukarram Zubair; Muhammad Irshad Baig; Nisar Ullah; Yasir Abbas; Almotasembellah Abushaban; Nadeem Baig (Desalination, 2026)

Optimizing Nitrogen Fertilization through Combined Sources and Split Humic Acid Application Improves Wheat Productivity and Stress Resilience in Semi-arid Soils - Tahir Fazal; Muhammad Aurangzaib; Umar Arshad; Rashid Iqbal; Muhammad Raheel; Allah Ditta; Mohamed Taha Yassin (Water, Air, & Soil Pollution, 2026)

Heat stress associated depression and allied affliction: Therapeutic roles of nutrition, micronutrients, and phytochemicals-a review - Taha Majid Mahmood Sheikh; Abdul Malik Tareen; Muhammad Asif Arain (International Journal of Biometeorology, 2026)

Exploration of molecular mechanisms responsible for arthritis alleviating attributes of Calliandra haematocephala extracts - Inaam Ur Rehman; Taha Muhammad; Abir Abdullah Alamro; Eman Hassan Alshehri; Hamza Ahmad Odeibat; Rodney B. Luwor; Adrian A. Achuthan; Mohammad Saleem; Mohamed Farouk Elsadek (Inflammopharmacology, 2026)

Olanzapine for chemotherapy-induced nausea and vomiting in breast cancer: a systematic review and meta-analysis of prospective randomised controlled trials - Syeda Masooma Jafri; Muhammad Shahzou Shah; Javeria Nawaz; Zainab Ali Siddiqui; Minhal Faisal; Abia Khalid Mir; Rana Taha Jamal (European Journal of Clinical Pharmacology, 2026)

Modelling methane production in trickle bed reactors: A biokinetic approach - Ahmed Taha; Muhammad Tahir Ashraf; Emil de Bekker Steffensen; Lars Yde; Jorge Rodríguez (Bioresource Technology, 2026)

Network pharmacology and molecular docking reveal PPARγ-directed antidiabetic phytochemical compounds of Momordica charantia - Owais; Israr Hussain; Muhammad Rahiyab; Arshad Iqbal; Syed Shujait Ali; Mohamed Taha Yassin (In Silico Pharmacology, 2026)

Retraction Note: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Experimental assessment of stirring effects in freeze desalination of brackish and seawater - Muhammad I. Rashad; Taha A. Elaghoury; Youssef Mohab; Lama A. Elsdeek; A.M. Kader; Shehab Ahmed; Mohamed A. Farahat (Desalination, 2026)

Molecular Detection and Phylogenetic Characterization of Avian Infectious Bronchitis Virus (IBV) in Vaccinated Commercial Chicken Flocks Experiencing Outbreaks in Faisalabad, Pakistan - Muhammad Mubeen Ahmad; Muhammad Wasif Gulzar; Muhammad Wasif Azeem; Muhammad Musa Mubashar; Rida Fatima; Muhammad Tayyab Naveed; Muhammad Taha; Sana Riaz; Asad Javed; Mudasser Habib; Rizwan Aslam (Archives of Virology, 2026)

Synergistic Role of Plant Growth-Promoting Rhizobacteria and Zinc Ferrite Nanoparticles in Mitigating Mercury Stress in Chickpea (Cicer arietinum L.) - Waqar Younas; Hina Khan; Humera Amin; Sami Ullah; Abd Ullah; Usman Ali; Muhammad Nafees; Fazal Amin; Iftikhar Ahmed; Tanveer Hussain; Mohamed Taha Yassin; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Environmental radiological evaluation of North and South industrial zones of Erbil city in terms of radon and gamma radiation levels from soils surface by using monte carlo simulation - Sardar Qader Othman; Taha Yaseen Wais; Berivan F. Namq; Taufiq Ahamad; Laith Ahmed Najam; Rohit Singh Sajwan; Muhammad Junaid; M. I. Sayyed (Environmental Geochemistry and Health, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

Mechanistic insight into inflammatory and oxidative stress ameliorating attributes of Atriplex crassifolia 70% ethanol extract against complete Freund’s adjuvant-induced arthritis - Jawaria Khurshid; Anam Iftikhar; Hamza Ahmad Odeibat; Eman Hassan Alshehri; Kiran Aslam; Maria Jaleel; Aymun Jawed; Muhammad Khalid Saeed; Rodney Luwor; Taha Muhammad; Mohammad Saleem; Mohamed Farouk Elsadek (Inflammopharmacology, 2025)

Recent research directions on functional royal jelly: highlights prospects in food, nutraceutical, and pharmacological industries - Muhammad H. Alu’datt; Doa’a Al-u’datt; Taha Rababah; Sana Gammoh; Mohammad Alrosan; Khalid Bani-Melhem; Yasmeen Al-widyan; Stan Kubow; Dana AbuJalban; Wesam Al Khateeb; Mais Abubaker (Critical Reviews in Food Science and Nutrition, 2025)

Resource recovery from potash brine effluent: integrated chemical precipitation and evaporative crystallization for zero liquid discharge and sustainable brine management - Youssef Amadghous; Yassine Ait-khouia; Abdelmaula Aboulaich; Abdelhak Zagriri; Muhammad Ouabid; Otmane Raji; Said Mansouri; Abdellatif Elghali; Yassine Taha; Mostafa Benzaazoua (Chemosphere, 2025)

Tobacco waste valorization through composting: A systematic review of biomass conversion efficiency and circular bioeconomy strategies - Yousif Abdelrahman Yousif Abdellah; Shimei Yang; Chengmo Yang; Zhenyan Yang; Elsiddig A.E. Elsheikh; Katharina Maria Keiblinger; Taha Ahmed Mohamed; Muhammad Shoaib Rana; Dong Liu; Fuqiang Yu (Biomass and Bioenergy, 2025)

Rhodanine-benzamides as potential hits for α-amylase enzyme inhibitors and radical (DPPH and ABTS) scavengers - Samuel Attah Egu; Irfan Ali; Khalid Mohammed Khan; Sridevi Chigurupati; Urooj Qureshi; Uzma Salar; Zaheer Ul-Haq; Suliman A. Almahmoud; Shatha Ghazi Felemban; Mohsin Ali; Muhammad Taha (Molecular Diversity, 2025)

Advancing algae-based Bioenergy: Techno-Economic assessment of hydrogen and biochar production from algal biomass - Aliyan Tanweer; Syed Ali Ammar Taqvi; Bilal Kazmi; Safiya Khatoon; Muhammad Taha; Muhammad Nadir; Farooq Ahmad; Naveed Ahmad (Biomass and Bioenergy, 2025)

Boosted wound healing and anticancer potential of polymer functionalized cerium oxide nanomaterials - Muhammad Khawar Abbas; Yasir Javed; Naveed Akhtar Shad; Azhar Rasul; Amna Bashir; Syed Fazil Bin Farukh; Heba Taha Abdulghani; Wasim Abbas; Aisha Sethi; Muhammad Ramzan Khawar; Dongwhi Choi (Journal of Trace Elements in Medicine and Biology, 2025)

Effect of selenium, sonication, and combination of selenium and sonication treatments on potassium bromate, alloxan, and titanium dioxide in bread - Sana Gammoh; Muhammad H. Alu'datt; Mohammad N. Alhamad; Taha Rababah; Mohammad Alrosan; Malak Shatarah (Food Chemistry, 2025)

Drug-eluting stent versus bare metal stent for symptomatic intracranial stenosis: a comparative systematic review and meta-analysis study - Mohammad Sina Mirjani; Pouria Delbari; Muhammad Hussain Ahmadvand; Saba Sabet; Zahra Ardestani; Mohammad Emad Sharifi; Sina Hatami; Mansoureh Jabari; Amirali Barkhordarioon; Mohammad Taha Akbari Javar; Amirmohammad Bahri; Sina Ahmadi; et al. (European Journal of Clinical Pharmacology, 2025)

Nutritional value and therapeutic applications of Chenopodium album for human and livestock health: A comprehensive review - Mohamed E. Abd El-Hack; Ahmed A. Allam; Ahmed K. Aldhalmi; Mahmoud Kamal; Muhammad Arif; Abdullah S. Alawam; Hassan A. Rudayni; Ayman E. Taha; Elwy A. Ashour; Mohammad M.H. Khan (Food Bioscience, 2025)

Immunomodulatory properties of a methanolic extract of Ficus lyrata mitigate inflammation in Complete Freund’s Adjuvant-induced arthritis - Anam Iftikhar; Mohammad Saleem; Syed Atif Raza; Adrian Achuthan; Rodney Luwor; Taha Muhammad; Umair Majeed (Inflammopharmacology, 2025)

RETRACTED ARTICLE: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Integrative metagenomic dissection of last-resort antibiotic resistance genes and mobile genetic elements in hospital wastewaters - Muhammad Shafiq; Xiaoling Guo; Meimei Wang; Hazrat Bilal; Li Xin; Yumeng Yuan; Fen Yao; Taha Majid Mahmood Sheikh; Muhammad Nadeem Khan; Xiaoyang Jiao (Science of The Total Environment, 2024)

Nematicidal Potential of Enzymatic Extracts of Pseudomonas aeruginosa and Bacillus cereus on Different Stages of Potato Cyst Nematode Globodera pallida - Abdelaziz Hajjaji; Ghita Ibnchekh; Taha Chouati; Bahia Rached; Muhammad Amjad Ali; Naima Rhallabi; Rajaa Ait Mhand; Fouad Mellouki (Journal of Crop Health, 2024)

Recent innovations and emerging technological advances used to improve quality and process of plant-based milk analogs - Taha Mehany; Shahida Anusha Siddiqui; Babatunde Olawoye; Oyekemi Olabisi Popoola; Abdo Hassoun; Muhammad Faisal Manzoor; Sneh Punia Bangar (Critical Reviews in Food Science and Nutrition, 2024)

Hydrothermal synthesis of ZnO@MoTe2 nanocomposite as excellent electrocatalyst for hydrogen evolution reaction (HER) - Saeed D. Alahmari; Salma Aman; Soumaya Gouadria; Sajjad Ahmad Khan; Abdullah G. Al-Sehemi; A.M.A. Henaish; Naseeb Ahmad; Zubair Ahmad; Taha Abdel Mohaymen Taha; Hafiz Muhammad Tahir Farid (Fuel, 2024)

Impact of ultrasonication on the contents, profiles and biofunctional properties of free and bound phenolics from white desert truffle (Tirmania nivea) and its protein fractions - Muhammad H. Alu'datt; Carole C. Tranchant; Mohammad N. Alhamad; Taha Rababah; Doa'a Al-U'datt; Sana Gammoh; Mohammad Alrosan; Sharifa Alkandari; Roa'a Zghoul (Food Research International, 2023)

Fundamental alteration of cellular biochemicals from attached microalgae onto palm kernel expeller waste upon optimizing the growth environment in forming adhesion complex - Hemamalini Rawindran; Kuan Shiong Khoo; Baranitharan Ethiraj; Uganeeswary Suparmaniam; Wai Hong Leong; Ratchaprapa Raksasat; Chin Seng Liew; Nurul Tasnim Sahrin; Man Kee Lam; Worapon Kiatkittipong; Jun Wei Lim; Zakariyya Uba Zango; et al. (Environmental Research, 2023)

Syntheses, in vitro, and in silico studies of rhodanine-based schiff bases as potential α-amylase inhibitors and radicals (DPPH and ABTS) scavengers - Samuel Attah Egu; Irfan Ali; Khalid Mohammed Khan; Sridevi Chigurupati; Urooj Qureshi; Uzma Salar; Muhammad Taha; Shatha Ghazi Felemban; Vijayan Venugopal; Zaheer Ul-Haq (Molecular Diversity, 2023)

Defective nickel zirconium oxide mesoporous bifunctional electrocatalyst for oxygen evolution reaction and overall water splitting - Maira Sadaqat; Sumaira Manzoor; Salma Aman; Laraib Nisar; Muhammad Najam-Ul-Haq; Afzal Shah; Ahmed M. Shawky; H. Elhosiny Ali; Muhammad Naeem Ashiq; T.A. Taha (Fuel, 2023)

A Click Synthesis, Molecular Docking and Biological Evaluation of 1,2,3-triazoles-benzoxazepine hybrid as potential anticancer agents - Muhammad Ashram; Almeqdad Y. Habashneh; Sanaa Bardaweel; Mutasem O. Taha (Medicinal Chemistry Research, 2023)

Two are better than one: the combinations of Beauveria bassiana, diatomaceous earth, and indoxacarb as effective wheat protectants - Waqas Wakil; Nickolas G. Kavallieratos; Erifili P. Nika; Abid Ali; Taha Yaseen; Muhammad Asrar (Environmental Science and Pollution Research, 2023)
The current study evaluates the efficacy of the entomopathogenic fungus Beauveria bassiana (Balsamo-Crivelli) Vuillemin (Hypocreales: Cordycipitaceae), diatomaceous earth (DE) (Protect-It), and the oxadiazine indoxacarb, at single or combined applications on wheat kernels, for the management of the rusty grain beetle, Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae), the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), and the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae). The study was conducted between November 2020 and August 2021 in Faisalabad under a complete randomized block design. The combination of DE + indoxacarb was the most efficient as it caused higher overall mortalities ranging between 59.34 and 100%, and lower overall progeny production ranging between 8.35 and 33.70 individuals per vial, than all other treatments. Beauveria bassiana alone exhibited the lowest mortality rates ranging between 22.33 and 47.76%, and the highest offspring emergence, ranging between 51.33 and 78.55 individuals per vial. Similar pattern was observed when persistence bioassays were conducted. For a period of 120 days, the DE + indoxacarb was the most powerful combination against all tested species, providing overall mortality rates between 17.06 and 63.80%. The overall progeny production was lower for the insect individuals exposed on wheat treated with the DE + indoxacarb combination, ranging between 13.66 and 52.23 individuals per vial, and higher for those exposed to B. bassiana alone, ranging between 44.03 and 107.67 individuals per vial, for the entire duration of storage. However, the efficacy of all treatments decreased gradually during the course of storage. The findings of the current study indicate that the combinations of entomopathogenic fungi, DE, and indoxacarb can be used for the prolonged protection of stored wheat from the tested noxious insect species of stored products. Further research, which will include other inert dusts in combination with entomopathogenic fungi and indoxacarb, may provide additional knowledge towards an effective management of noxious species occurring in storages.

Evaluating the safety and efficacy of daprodustat for anemia of chronic kidney disease: a meta-analysis of randomized clinical trials - Kaneez Fatima; Warda Ahmed; Asad Saulat Fatimi; Omar Mahmud; Muhammad Umar Mahar; Ayesha Ali; Syed Roohan Aamir; Muhammad Taha Nasim; Muhammad Bilal Islam; Muhammad Talha Maniya; Dua Azim; Shayan Marsia; et al. (European Journal of Clinical Pharmacology, 2022)

Combinations of Beauveria bassiana and spinetoram for the management of four important stored-product pests: laboratory and field trials - Waqas Wakil; Nickolas G. Kavallieratos; Erifili P. Nika; Mirza Abdul Qayyum; Taha Yaseen; Muhammad Usman Ghazanfar; Muhammad Yasin (Environmental Science and Pollution Research, 2022)
The current study examines the efficacy of the semi-synthetic insecticide spinetoram and entomopathogenic fungi Beauveria bassiana (Balsamo-Crivelli) Vuillemin (Hypocreales: Cordycipitaceae) as wheat protectants against the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae), the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), the granary weevil, Sitophilus granarius (L.) (Coleoptera: Curculionidae), and the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), under laboratory and field trials. One dose of B. bassiana , i.e., 1 × 10 7 conidia/kg wheat, two doses of spinetoram, i.e., spine1: 0.05 ppm (mg/kg wheat), spine2: 0.1 ppm, and their combinations (Bb + spine1, Bb + spine2) were evaluated at 20, 25, and 30 °C. All treatments provided significantly higher mortality at 30 °C compared with the other two temperatures. Maximum mortality levels were observed in the treatments where B. bassiana was combined with the higher dose of spinetoram (0.1 ppm). All treatments reduced progeny production in comparison with the control groups. Maximum progeny reduction was observed at 30 °C, on wheat treated with the Bb + spine2 combination. The combination Bb + spine2 also provided elevated mortality rates in both laboratory and field persistence trials, but at 180 days caused moderate mortality to all tested insect species. Concerning progeny, at laboratory persistence trials, the combination Bb + spine2 exhibited the lowest offspring emergence to all tested species compared to the other treatments and control. Overall, our study showed that R. dominica was the most susceptible species followed by S. granarius , T. castaneum , and T. granarium . Our findings revealed that the combination of B. bassiana and spinetoram may be a useful tool for efficient and advanced integrated pest management strategies for long storage periods under multiple temperatures.

Dihydroquinazolin-4(1H)-one derivatives as novel and potential leads for diabetic management - Oluwatoyin Babatunde; Shehryar Hameed; Uzma Salar; Sridevi Chigurupati; Abdul Wadood; Ashfaq Ur Rehman; Vijayan Venugopal; Khalid Mohammed Khan; Muhammad Taha; Shahnaz Perveen (Molecular Diversity, 2022)

Synthesis, β-glucuronidase inhibition and molecular docking studies of cyano-substituted bisindole hydrazone hybrids - Obaidurahman Abid; Syahrul Imran; Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Syed Muhammad Kashif; Khalid Mohammed Khan; Juliana Yusoff (Molecular Diversity, 2021)

Biology-oriented drug synthesis (BIODS), in vitro urease inhibitory activity, and in silico studies on ibuprofen derivatives - Faiza Seraj; Kanwal; Khalid Mohammed Khan; Ajmal Khan; Muhammad Ali; Ruqaiya Khalil; Zaheer Ul-Haq; Shehryar Hameed; Muhammad Taha; Uzma Salar; Shahnaz Perveen (Molecular Diversity, 2021)

Identification of archeological sites threatened with obliteration using space-borne and ground penetrating radars data in site of Tulul al-Ukhaidir, Iraq - Zaidoon Taha Abdulrazzaq; Jassim Muhammad Thabit; Ammar Jasim Al-Khafaji (Applied Geomatics, 2019)

Synthesis, α-amylase inhibition and molecular docking study of bisindolylmethane sulfonamide derivatives - Muhammad Taha; Tayyaba Noreen; Syahrul Imran; Fasial Nawaz; Sridevi Chigurupati; Manikandan Selvaraj; Fazal Rahim; Nor Hadiani Ismail; Ashok Kumar; Ashik Mosaddik; Abdullah M. Alghamdi; Yousif Abdulrahman nasser alqahtani; et al. (Medicinal Chemistry Research, 2019)

Oxindole-based chalcones: synthesis and their activity against glycation of proteins - Ayesha Khan; Ajmal Khan; Umar Farooq; Muhammad Taha; Syed Adnan Ali Shah; Sobia Ahsan Halim; Arfa Akram; Mohammed Ziauddin Khan; Abdul Khaliq Jan; Ahmed Al-Harrasi (Medicinal Chemistry Research, 2019)

Occurrence, types, properties and interactions of phenolic compounds with other food constituents in oil-bearing plants - Muhammad H. Alu'datt; Taha Rababah; Mohammad N. Alhamad; Ghaid J. Al-Rabadi; Carole C. Tranchant; Ali Almajwal; Stan Kubow; Inteaz Alli (Critical Reviews in Food Science and Nutrition, 2018)

Synthesis, in vitro $$α $$ α -glucosidase inhibitory activity, and in silico study of (E)-thiosemicarbazones and (E)-2-(2-(arylmethylene)hydrazinyl)-4-arylthiazole derivatives - Muhammad Ali; Khalid Mohammed Khan; Uzma Salar; Mohammed Ashraf; Muhammad Taha; Abdul Wadood; Sujhla Hamid; Muhammad Riaz; Basharat Ali; Shahbaz Shamim; Farman Ali; Shahnaz Perveen (Molecular Diversity, 2018)

Synthesis of 2-phenyl-1H-imidazo[4,5-b]pyridine as type 2 diabetes inhibitors and molecular docking studies - Muhammad Taha; Nor Hadiani Ismail; Syahrul Imran; Izzatul Ainaa; Manikandan Selvaraj; Mohd syukri baharudin; Muhammad Ali; Khalid Mohammed Khan; Nizam Uddin (Medicinal Chemistry Research, 2017)

Syntheses, in vitro evaluation and molecular docking studies of 5-bromo-2-aryl benzimidazoles as α-glucosidase inhibitors - Tanzila Arshad; Khalid Mohammed Khan; Najma Rasool; Uzma Salar; Shafqat Hussain; Tehreem Tahir; Mohammed Ashraf; Abdul Wadood; Muhammad Riaz; Shahnaz Perveen; Muhammad Taha; Nor Hadiani Ismail (Medicinal Chemistry Research, 2016)

Synthesis of 2-(2-methoxyphenyl)-5-phenyl-1,3,4-oxadiazole derivatives and evaluation of their antiglycation potential - Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Syahrul Imran; Fazal Rahim; Syed Muhammad Kashif; Mohd Zulkefeli (Medicinal Chemistry Research, 2016)

Synthesis and evaluation of unsymmetrical heterocyclic thioureas as potent β-glucuronidase inhibitors - Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Khalid Mohammed Khan; Uzma Salar; Syed Muhammad Kashif; Fazal Rahim; Yawar Latif (Medicinal Chemistry Research, 2015)

Synthesis of phenyl thiazole hydrazones and their activity against glycation of proteins - Khalid Mohammed Khan; Muhammad Irfan; Mahwish Ashraf; Muhammad Taha; Syed Muhammad Saad; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Erratum to: Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid Mohammed Khan; Sammer Yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid M. Khan; Sammer yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Synthesis of indole-2-hydrazones in search of potential leishmanicidal agents - Muhammad Taha; Nor Hadiani Ismail; Muhammad Ali; Khalid M. Khan; Waqas Jamil; Syed Muhammad Kashif; Mohammad Asraf (Medicinal Chemistry Research, 2014)

2-(2′-Pyridyl) benzimidazole derivatives and their urease inhibitory activity - Zafar Saeed Saify; Arfa Kamil; Shamim Akhtar; Muhammad Taha; Ajmal Khan; Khalid Mohammed Khan; Sarwat Jahan; Fazal Rahim; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2014)

Optimisation and characterisation of various extraction conditions of phenolic compounds and antioxidant activity in olive seeds - Muhammad H. Alu’datt; Inteaz Alli; Khalil Ereifej; Mohammad N. Alhamad; Ahmad Alsaad; Taha Rababeh (Natural Product Research, 2011)

Antioxidant activities, total phenolics and HPLC analyses of the phenolic compounds of extracts from common Mediterranean plants - Taha M. Rababah; Khalil I. Ereifej; Ranya B. Esoh; Muhammad H. Al-u'datt; Mohammad A. Alrababah; W. Yang (Natural Product Research, 2011)

Leishmanicidal potential of N-substituted morpholine derivatives: Synthesis and structure–activity relationships - Khalid Mohammed Khan; Muhammad Zarrar Khan; Muhammad Taha; Ghulam Murtaza Maharvi; Zafar Saeed Saify; Shahnaz Parveen; Muhammad Iqbal Choudhary (Natural Product Research, 2009)

Numerical analysis of effective soil porosity and soil thickness effects on slope stability at a hillslope of weathered granitic soil formation - Muhammad Mukhlisin; Mohd Raihan Taha; Ken’ichirou Kosugi (Geosciences Journal, 2008)